2018
DOI: 10.1093/cvr/cvy036
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Sirt3 accelerates arterial thrombosis by increasing formation of neutrophil extracellular traps and plasma tissue factor activity

Abstract: AimsSirtuin 3 (Sirt3) is a mitochondrial, nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase that reduces oxidative stress by activation of superoxide dismutase 2 (SOD2). Oxidative stress enhances arterial thrombosis. This study investigated the effects of genetic Sirt3 deletion on arterial thrombosis in mice in an inflammatory setting and assessed the clinical relevance of these findings in patients with ST-elevation myocardial infarction (STEMI).Methods and resultsUsing a laser-induced carotid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…However, some studies also show that sirtuins, especially Sirt1 and Sirt3, are involved in thromboprotection. The authors not only correlated the loss of sirtuins with the promotion of arterial thrombosis, but also demonstrated that their inhibition is linked to an elevated level of TF ( Breitenstein et al, 2011 ; Gaul et al, 2018 ). In addition, Gaul et al (2018) reported that arterial thrombosis in mice with Sirt3 knockout is enhanced with an increased formation of NETs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, some studies also show that sirtuins, especially Sirt1 and Sirt3, are involved in thromboprotection. The authors not only correlated the loss of sirtuins with the promotion of arterial thrombosis, but also demonstrated that their inhibition is linked to an elevated level of TF ( Breitenstein et al, 2011 ; Gaul et al, 2018 ). In addition, Gaul et al (2018) reported that arterial thrombosis in mice with Sirt3 knockout is enhanced with an increased formation of NETs.…”
Section: Discussionmentioning
confidence: 98%
“… Breitenstein et al (2011) showed that the inhibition of Sirt1 contributes to arterial thrombosis associated with the increased activation of nuclear factor-kappa B/p65, leading to augmented TF activity. Similarly, Gaul et al (2018) noticed that genetic loss of Sirtuin 3 results not only in enhanced TF activity, but also increases the formation of NETs that together lead to the promotion of arterial thrombosis. Little is known about the impact of IS on sirtuins.…”
Section: Introductionmentioning
confidence: 98%
“…Coagulation abnormalities in Pon 2‐deficient mice are indicated by shortened clotting times in vitro , likely reflecting pre‐activated coagulation factors, and are reversed by restoration of PON2 expression in endothelial cells . Deficiency of sirtuin 3 (Sirt3), another anti‐oxidative molecule inactivating superoxide dismutase 2 (SOD2), increases myeloid cell TF prothrombotic function in experimental murine thrombosis in vivo in the context of inflammation induced by endotoxin . The previously underappreciated expression of TF by endothelial cells plays a major role in sickle cell disease (SCD) pathology.…”
Section: Cell Type‐specific Roles Of Tf In Thrombosis and Hemostasismentioning
confidence: 99%
“…As previously described [21], mice received 5 mg/kg lipopolysaccharide (LPS) (E. coli O111: B4, Sigma-Aldrich, St. Louis, MO, USA) by intraperitoneal (i.p.) injection 10 h before the laser-induced arterial thrombosis to trigger inflammation.…”
Section: Treatments and Arterial Thrombosismentioning
confidence: 99%
“…Murine thrombosis experiments sought to mimic an underlying inflammatory condition by administering LPS, as done previously [21]. Next, animals received the canakinumab-surrogate antibody (01BSUR, 10 µg/g) and underwent the thrombosis protocol (Figure 2A).…”
Section: Il-1β Neutralization Delays Arterial Thrombotic Occlusion Inmentioning
confidence: 99%